Clinical practice and outcomes in elderly STEMI patients undergoing PCI with new generation DES – data from a large worldwide registry. (25th November 2020) - Roguin, A
Abstract: Background: The best treatment option for elderly patients with acute myocardial infarction (MI) remains unclear. Purpose: We aimed to determine clinical practice and outcomes of PCI with a new generation DES in patients with ST-elevated MI (STEMI), aged ≥80 years included in a one of the largest real-world PCI registries. Methods: e-Ultimaster is a prospective, world-wide, multi-centre registry that enrolled 36, 671 patients with coronary artery disease, treated with a thin strut sirolimus-eluting stent with abluminal bioresorbable polymer coating, across 50 countries. 34, 538 patients who completed 1-year follow-up or who died were included in the analysis. The primary endpoint was 1-year target lesion failure (TLF: cardiac death, target vessel (TV) MI, clinically driven (CD) target lesion revascularization (TLR)). An Clinical Event Committee adjudicated all endpoint-related adverse events. Results: 6863 presented with STEMI at baseline (19.9%). Mean age of STEMI patients was 61.0±11.7 years, with 78.8% males. Diabetes was present in 20.9% and hypertension in 52.4%. Of 6863 STEMI patients, 430 patients (6.2%) were aged ≥80 years, with 46.5% females compared to 19.5% females in the younger group. Patients in the older group had more comorbidities (hypertension and renal impairment) and more often took oral anticoagulant medication (9.2% vs 3.9%; p<0.001). At discharge 94.9% of older STEMI patients were on dual antiplatelet therapy (DAPT) as compared to 97.6% of younger STEMI patients (p=0.002). Older STEMI patients more often took clopidogrel as second antiplatelet agent (54.7% vs 39.8%; p<0.001) and were less often on prasurgrel (2.3%vs 10.9%; p<0.001) and ticagrelor (41.2% vs 48.1%; p=0.005). STEMI patients in the older group more often had multivessel disease (52.1 vs 45.8%; p=0.01), treatment of the left main artery (4.7 vs 1.4%; p<0.001) and more calcified lesions (18.8 vs 11.2%; p<0.001). Other lesion characteristics were similar between the two groups. Preferred access approach was radial and was alike in the two groups (87.0 vs 84.0%; p=0.10) In-hospital mortality was more frequent in older STEMI patients (2.3% vs 0.8%; p=0.003). More bleedings were observed in older vs younger STEMI patients at discharge. One-year TLF was significantly higher in older age group (7.0% vs 3.0%; p<0.01), mainly driven by increased rates of cardiac death. All-cause mortality and bleedings were also more frequent in older STEMI patients. No differences were observed in revascularization or ST rates (1.4 vs 1.1%; p=0.48). Conclusions: In elderly patients with STEMI, in-hospital mortality rates as well as bleeding rates were higher as compared to younger patients, while 1-year rates of revascularization and ST did not differ between the groups. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Terumo Europe